Modified and unmodified arabinoxylans from Plantago ovata husk: Novel excipients with antimicrobial potential (Bangladesh Journal of Pharmacology, 2015)
Arabinoxylan is a polysaccharide of Plantago ovata, an indigenous plant of Pakistan and several European countries. In the present investigation arabinoxylan isolated from P. ovata husk was chemically modified i.e., carboxymethylated and was converted into its sodium salt. Physicochemical characterization of modified arabinoxylans was done. The antimicrobial assay of arabinoxylan and modified arabinoxylans was done by Kirby-Bauer disk diffusion method against Gram negative and Gram positive bacterial strains. Physicochemical properties of modified arabinoxylans were different from arabinoxylan yet were satisfactory for their use as pharmaceutical excipients.  Arabinoxylan showed strong antimicrobial activity against Gram positive strains.  However, it showed no antimicrobial activity against Gram negative strains. Carboxymethyl arabinoxylan showed maximum activity against S. epidermidis. It also showed activity against S. aureus and P. aeruginosa.  Arabinoxylan-Na showed concentration-dependent antimicrobial activity. This study provides the first report on the antibacterial properties of arabinoxylan and its modified forms.